Efektivitas audiovisual berbantuan QR-Code dalam pembelajaran teks eksplanasi di SMKN 1 Simpang Rimba - Septiani, Yani (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research was conducted on the lack of interest and enthusiasm of the students in the use of learning media that affect student learning outcomes. The goal is how far the effectiveness of the QR Code in understanding the explanatory text at SMK Negeri 1 Simpang Rimba, South Bangka. This learning is based on the theory of learning approach based on higher order thinking skills. This research method uses One Shot Case Study. The research data are in the form of pretest and posttest that understanding the explanatory text in formative test with high level questions and questionnaires. The results of the study are showing video footage with QR Code is more effective in understanding explanatory text and it can help students think critically. It can be concluded that QR-Code assisted audiovisual can improve student learning outcomes.